2004
DOI: 10.1103/physrevb.70.201202
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature ferromagnetism in (Ga, Mn)N: Ab initiocalculations

Abstract: The magnetic properties of dilute magnetic semiconductors (DMSs) are calculated from first-principles by mapping the ab initio results on a classical Heisenberg model. By using the Korringa-Kohn-Rostoker coherent-potential approximation (KKR-CPA) method within the local-density approximation, the electronic structure of (Ga, Mn)N and (Ga, Mn)As is calculated. Effective exchange coupling constants J ij 's are determined by embedding two Mn impurities at sites i and j in the CPA medium and using the J ij formula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
215
2
2

Year Published

2005
2005
2009
2009

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 294 publications
(249 citation statements)
references
References 38 publications
30
215
2
2
Order By: Relevance
“…We confirmed this by calculations ͑not shown here in detail͒ of the total energy of the ferromagnetic state, E ferro , versus the disordered-localmoment state energy, E DLM ; the latter is represented in the CPA by an alloy of the type MgO 1−x N 0.5x ↑ N 0.5x ↓ , where N ↑ and N ↓ are impurities with magnetic moment pointing "up" and "down." 22 As is typical for double-exchange DMS systems, 16 we found that the energy gain of the ferromagnetic state, E DLM − E ferro , scales with the square root of the concentration. Further confirmation on the ferromagnetic nature of the ground state comes from calculations of the exchange constants, to be presented in the next section.…”
Section: Ground-state Electronic and Magnetic Structuresmentioning
confidence: 83%
See 1 more Smart Citation
“…We confirmed this by calculations ͑not shown here in detail͒ of the total energy of the ferromagnetic state, E ferro , versus the disordered-localmoment state energy, E DLM ; the latter is represented in the CPA by an alloy of the type MgO 1−x N 0.5x ↑ N 0.5x ↓ , where N ↑ and N ↓ are impurities with magnetic moment pointing "up" and "down." 22 As is typical for double-exchange DMS systems, 16 we found that the energy gain of the ferromagnetic state, E DLM − E ferro , scales with the square root of the concentration. Further confirmation on the ferromagnetic nature of the ground state comes from calculations of the exchange constants, to be presented in the next section.…”
Section: Ground-state Electronic and Magnetic Structuresmentioning
confidence: 83%
“…[16][17][18] The scope of this paper is to investigate the appearance and stability of the ferromagnetic state, including calculations for the Curie temperature, in MgO 1−x N x compounds for x Ͻ 15%, in view of recent experimental activities with respect to the particular system. 19 Our focus is on the solution provided by local density-functional theory ͑DFT͒, presented in Sec.…”
Section: Introductionmentioning
confidence: 99%
“…18,19,20,21,22,23,24,25,26 Some predict an alternating sign for the exchange coupling, but these predictions should be taken with extreme care, since these theoretical calculations are based on non-fullpotential muffin-tin-type potentials which are not reliable to treat the electronic structure of covalent semiconductor systems such as (Ga,Mn)As DMS. Also, disorder quite certainly is not adequately taken into account within simple effective-medium approaches such as VCA or CPA, as fluctuations in the Mn positions essentially lead to variations in the Mn-Mn exchange-coupling parameters, as apparent from Fig.…”
Section: The Dependence Of Jn With the Concentrationmentioning
confidence: 99%
“…In a series of theoretical studies, in which the effect of randomness/disorder is described by the coherent-potential approximation (CPA), Kudrnovský et al 19,20 and Bergqvist et al 21 have used a tight-binding linear muffin-tin orbital method, together with the magnetic force theorem, to study the dependence of the Mn-Mn exchange couplings and critical temperatures with the concentration of Mn impurities in III-V and group IV DMS. Also, Sato et al 22,23 have used muffin-tin type potentials together with a KKR-CPA approach to study Curie temperatures and exchange interactions in III-V DMS. Moreover, Sandratskii and Bruno 24,25,26 have used the augmentedspherical-wave method within the local-density approxi-mation to investigate exchange interactions, Curie temperatures and the influence of the clustering of Mn impurities in (Ga,Mn)As.…”
mentioning
confidence: 99%
“…Indeed, a large number of first-principles calculations showed that these materials have very high Curie temperatures. [87][88][89][90][91][92][93] As mentioned in preceding part, the direction of the conduction electron spin polarization with respect to the local moment and its amplitude are important in classifying ferromagnets. From the obtained results, the full-Heusler alloys can be characterized as weak ferromagnets since the spin polarization is negative for all Z constituents, i.e., sp-d mixing is dominating.…”
Section: Conduction Electron Spin Polarizationmentioning
confidence: 99%